The effect of: Metritis, Retained placenta, Inactive ovaries on reproductive performance in dairy cows. - جبور, زهير ابراهيم (Latakia University Journal -Biological Sciences Series, 2020)
The research aimed to determine the influence of: Retained Placenta, Metritis and Ovarian inactivity on some reproductive indicators in the postpartum period in dairy cows, which include: Insemination index, Days to first service, Days to conception, Interval between two calving’s. For this purpose was studied herd consist of (66) Holstein-Friesian cows, which were divided into following groups: control (n=14), with retained placenta (n=17), with metritis (n=18), with ovarian inactivity (n=17). The results showed that, the Insemination index was for Retained Placenta, Metritis, and Ovarian inactivity, and Control: 2.76±1.20, 3.11 ±1.78, 3.18 ±1.63, 1.64 ±0.63 respectively. There were no differences between first three groups, which were greater compared with control (p<0.05). The period to first service was for Retained Placenta, and Metritis, and Ovarian inactivity, and Control: 62.65 ±10.56, 64.22 ±18.95, 74.12 ±18.27, and 55.79±13.54 respectively. There was significant difference (p < 0.05) between first three groups and the control. The period to conception was for Retained Placenta, and Metritis, and ovarian inactivity, and Control: 210.50 ±31.65, 204.70 ±101.40, 264.80 ±95.20, and 96.75 ±57.59 respectively. There was significant difference (p < 0.05) between first three groups and the control. The interval between two calving was for Retained Placenta, and Metritis, and ovarian inactivity, and Control: 472.25 ±36.32, 465.50 ±104.01531.60 ±95.05, 366.58 ±56.05 respectively. There was significant difference (p < 0.05) between first three groups and the control.